A performance comparison of flat and cluster based routings in mobile ad hoc networks - Yu, Jane Y. (2013)
The objective of this paper is to study the performance comparison between flat and cluster-based routings in MANETs. Previous study shows that an earlier proposed cluster-based routing, Cluster based Routing Protocol (CBRP), has poorer performance due to its inefficient clustering algorithms based on Least Clusterhead Change (LCC) and Lowest ID (LID). Thus, in this paper, we first propose a new cluster-based routing, namely efficient cluster based routing protocol (ECBRP), which is based on a more efficient and stable clustering scheme. In addition, a new information table update mechanism utilizing routing events and data forwarding events is introduced in ECBRP to enhance the clustering and routing performance. The performance comparison in terms of packet delivery ratio and normalized routing overhead between flat and cluster based routings are studied extensively. Two flat routings (Dynamic Source Routing (DSR) and Ad Hoc On-demand Distance Vector (AODV)) and two cluster-based routing (CBRP and ECBRP) under various scenarios such as traffic load, mobility, network size and network area are considered in our study. By evaluating the performance of ECBRP and CBRP, we can study how the performance of a CBRP is affected by its underlying cluster structure. Simulation results show that ECBRP can achieve satisfying routing performance and outperform other routing schemes, DSR, AODV and CBRP, under the same simulated scenarios.